Target tracking using deep neural network (DNN) - Hu, Minghui (2019)
Deep learning is widely used in recent years, and the application of machine learning techniques in computer vision like object detection and tracking has been a prime part in this field. This project mainly introduces a method of a recurrent convolution neural network for object detection and tracking in dim light underwater condition. The convolution neural network model is inspired by a spatially supervised regression method, while the recurrent part is based on bounding box recurrent methods like Long Short-Term Memory and Gated Recurrent Units. This project conducts a systematically analysis on YOLO and LSTMs model. We illustrate our methods on an annotated dataset consisting of massive underwater footage. Experimental results show that recurrent convolution neural network can complete the object detection and regression method can meet the tracking requirement and boost the stability of the system.